The MEG3/miR-133b regulatory axis in exosomes influences macrophage responses to drug-resistant mycobacterium tuberculosis - Chuanqi Zou; Boxin Wang; Chengguang Wang; Jingjin Ma; Xinyu Yang; Junhong Chen; Zhengxue Quan; Wenjie Wu (Archives of Microbiology, 2026)

Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

Tumor empowered binary macrophages regulate T cell interferon signaling to mediate immunotherapy resistance in gastric cancer - Tong Xie; Bohan Zhang; Lei Jiang; Wenwen Zhang; Boxin Liu; Yang Shi; Xiaotian Zhang; Jian Li; Yifan Zhang; Jun Zhou; Yanshuo Cao; Yakun Wang; et al. (Science Bulletin, 2026)

Time Prediction in Ship Block Manufacturing Based on Transfer Learning - Jinghua Li; Pengfei Lin; Dening Song; Zhe Yan; Boxin Yang; Lei Zhou (Journal of Marine Science and Engineering, 2024)
Accurate time prediction is critical to the success of ship block manufacturing. However, the emergence of new ship types with limited historical data poses challenges to existing prediction methods. In response, this paper proposes a novel framework for ship block manufacturing time prediction, integrating clustering and the transfer learning algorithm. Firstly, the concept of distributed centroids was innovatively adopted to achieve the clustering of categorical attribute features. Secondly, abundant historical data from other types of blocks (source domain) were incorporated into the neural network model to explore the effects of block features on manufacturing time, and the model was further transferred to blocks with limited data (target domain). Leveraging the similarities and differences between source and target domain blocks, actions involving freezing and fine-tuning parameters were adopted for the predictive model development. Despite a small sample size of only 80, our proposed block time prediction method achieves an impressive mean absolute percentage error (MAPE) of 8.62%. In contrast, the MAPE for the predictive model without a transfer learning algorithm is notably higher at 14.97%. Experimental validation demonstrates the superior performance of our approach compared to alternative methods in scenarios with small sample datasets. This research addresses a critical gap in ship block manufacturing time prediction.

Design and analysis of quorum sensing language “Interpreter” ecosystem for microbial community - Shengbo Wu; Hong Zhang; Yongsheng Zhou; Chengyang Xu; Boxin Yuan; Haijiao Wang; Danlei Chen; Chunjiang Liu; Qinggele Caiyin; Hao Wu; Aidong Yang; Kun Zhao; et al. (Chemical Engineering Journal, 2024)

Highly conductive, super-stretchable and stable stretchable conductor with CNT and liquid metal alternating layered structure - Changshun Gu; Wenjing Qin; Xiujie Guo; Boxin Zhao; Yanli Wang; Xinxin Li; Mengyao Chen; Liying Yang; Shougen Yin (Chemical Engineering Journal, 2024)

Circ DENND4C inhibits pyroptosis and alleviates ischemia-reperfusion acute kidney injury by exosomes secreted from human urine-derived stem cells - Boxin Yang; Junxiong Wang; Jiao Qiao; Qian Zhang; Qi Liu; Yuan Tan; Qingchen Wang; Wenyuan Sun; Weimin Feng; Zhongxin Li; Chong Wang; Shuo Yang; et al. (Chemico-Biological Interactions, 2024)

CDC20 promotes radioresistance of prostate cancer by activating Twist1 expression - Chuanlai Yang; Yuegang Ge; Yachen Zang; Ming Xu; Lu Jin; Yang Wang; Xinyu Xu; Boxin Xue; Zhiwei Wang; Lixia Wang (Apoptosis, 2023)

Human CYP1B1 enzyme-mediated, AhR enhanced activation of aflatoxin B1 for its genotoxicity in human cells - Yuting Chen; Zhaohong Lu; Boxin Li; Huanhuan Wang; Tikeng Jiang; Mei Xuan; Hui Yang; Jialong Chen; Xiaoshan Liu; Hairong Liang; Yungang Liu; Huanwen Tang (Toxicology Letters, 2023)

Iron plaque effects on selenium and cadmium stabilization in Cd-contaminated seleniferous rice seedlings - Hongyu Zhang; Shuyun Xie; Neng Wan; Boxin Feng; Qi Wang; Kangjun Huang; Yang Fang; Zhengyu Bao; Feng Xu (Environmental Science and Pollution Research, 2022)

Characterization and comparison of two C-type lectins with novel key motifs from mud crab Scylla paramamosain - Boxin Zeng; Taiwei Dong; Yanting Xia; Shun Yang; Mengmeng Huang; Hui Fei (Journal of Oceanology and Limnology, 2022)